Postural and Musculoskeletal Disorders in Women with Urinary Incontinence: A Research Report - Dehghan Manshadi, Farideh; Ghanbari, Zinat; Miri, Elaheh-Sadat; Azimi, Hadi (Journal of Clinical Physiotherapy Research, 2016)
Introduction: To investigate and compare the prevalence of some postural and musculoskeletal disorders in women with and without Urinary Incontinence (UI). Urinary Incontinence (UI) is one of the most important social and health problems in women. Limited studies have shown that UI prevalence is around 35%-55% in Iran. Nevertheless, to the best of our knowledge, there is no exact and reliable data reported in the literature on the prevalence of musculoskeletal, postural, or other related disorders in UI patients in Iran. Methods and Materials: The current study was conducted based on the data obtained from 166 incontinent and 90 continent women attending Vali-e-Asr University Hospital between 2010 and 2012. After collecting participants’ demographic information, postural status was assessed. In addition, we measured values for pelvic inclination and lumbar lordosis angles. Finally, vaginal tone and pelvic floor muscle strength and endurance were evaluated. Kolmogorov-Smirnov (K-S) goodness-of-fit, Independent t, X2, and Pearson correlation tests were used for the purposes of data analysis. Results: The prevalence of low back pain, chronic pelvic pain, and pelvic asymmetry were significantly higher in incontinent women compared with that in continent women (p<0.05). It was found that lumbar lordosis was significantly different between the two groups (P=0.021); however, no significant difference was observed regarding pelvic inclination (P=0.20). Conclusion: The present study confirms the hypothesis that incontinent women have higher prevalence of low back and pelvic pain and pelvic asymmetry. It is recommented that further epidemiologic and comprehensive etiologic investigations be conducted on these findings. Keywords: Urinary Incontinence, Posture, Musculoskeletal Disorders, Women